Difference between revisions of "009A Sample Final 1, Problem 7"
Jump to navigation
Jump to search
(2 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
<span class="exam">A curve is defined implicitly by the equation | <span class="exam">A curve is defined implicitly by the equation | ||
− | + | ::<math>x^3+y^3=6xy.</math> | |
− | <span class="exam">a) Using implicit differentiation, compute & | + | <span class="exam">(a) Using implicit differentiation, compute <math style="vertical-align: -12px">\frac{dy}{dx}</math>. |
− | <span class="exam">b) Find an equation of the tangent line to the curve <math style="vertical-align: -4px">x^3+y^3=6xy</math> at the point <math style="vertical-align: -5px">(3,3)</math>. | + | <span class="exam">(b) Find an equation of the tangent line to the curve <math style="vertical-align: -4px">x^3+y^3=6xy</math> at the point <math style="vertical-align: -5px">(3,3)</math>. |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |'''1.''' What is the result of implicit differentiation of <math style="vertical-align: -4px">xy?</math> | + | |'''1.''' What is the result of implicit differentiation of <math style="vertical-align: -4px">xy?</math> |
|- | |- | ||
| | | | ||
− | + | It would be <math style="vertical-align: -13px">y+x\frac{dy}{dx}</math> by the Product Rule. | |
|- | |- | ||
|'''2.''' What two pieces of information do you need to write the equation of a line? | |'''2.''' What two pieces of information do you need to write the equation of a line? | ||
|- | |- | ||
| | | | ||
− | + | You need the slope of the line and a point on the line. | |
|- | |- | ||
|'''3.''' What is the slope of the tangent line of a curve? | |'''3.''' What is the slope of the tangent line of a curve? | ||
|- | |- | ||
| | | | ||
− | + | The slope is <math style="vertical-align: -13px">m=\frac{dy}{dx}.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 33: | Line 34: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |Using implicit differentiation on the equation& | + | |Using implicit differentiation on the equation <math style="vertical-align: -4px">x^3+y^3=6xy,</math> we get |
|- | |- | ||
| | | | ||
− | + | <math>3x^2+3y^2\frac{dy}{dx}=6y+6x\frac{dy}{dx}.</math> | |
|} | |} | ||
Line 42: | Line 43: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we move all the & | + | |Now, we move all the <math style="vertical-align: -12px">\frac{dy}{dx}</math> terms to one side of the equation. |
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>3x^2-6y=\frac{dy}{dx}(6x-3y^2).</math> | |
+ | |- | ||
+ | |We solve to get | ||
|- | |- | ||
− | | | + | | <math style="vertical-align: -17px">\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}.</math> |
|} | |} | ||
Line 57: | Line 60: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we find the slope of the tangent line at the point & | + | |First, we find the slope of the tangent line at the point <math style="vertical-align: -5px">(3,3).</math> |
|- | |- | ||
− | |We plug <math style="vertical-align: -5px">(3,3)</math>& | + | |We plug <math style="vertical-align: -5px">(3,3)</math> into the formula for <math style="vertical-align: -12px">\frac{dy}{dx}</math> we found in part (a). |
|- | |- | ||
|So, we get | |So, we get | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
+ | \displaystyle{m} & = & \displaystyle{\frac{3(3)^2-6(3)}{6(3)-3(3)^2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{-\frac{9}{9}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{-1.} | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 70: | Line 79: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we have the slope of the tangent line at <math style="vertical-align: -5px">(3,3)</math>& | + | |Now, we have the slope of the tangent line at <math style="vertical-align: -5px">(3,3)</math> and a point. |
|- | |- | ||
|Thus, we can write the equation of the line. | |Thus, we can write the equation of the line. | ||
|- | |- | ||
− | |So, the equation of the tangent line at <math style="vertical-align: -5px">(3,3)</math>& | + | |So, the equation of the tangent line at <math style="vertical-align: -5px">(3,3)</math> is |
|- | |- | ||
| | | | ||
− | + | <math>y\,=\,-1(x-3)+3.</math> | |
− | |||
− | |||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)'''& | + | | '''(a)''' <math>\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}</math> |
|- | |- | ||
− | |'''(b)'''& | + | | '''(b)''' <math>y=-1(x-3)+3</math> |
|} | |} | ||
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 08:13, 10 April 2017
A curve is defined implicitly by the equation
(a) Using implicit differentiation, compute .
(b) Find an equation of the tangent line to the curve at the point .
Foundations: |
---|
1. What is the result of implicit differentiation of |
It would be by the Product Rule. |
2. What two pieces of information do you need to write the equation of a line? |
You need the slope of the line and a point on the line. |
3. What is the slope of the tangent line of a curve? |
The slope is |
Solution:
(a)
Step 1: |
---|
Using implicit differentiation on the equation we get |
|
Step 2: |
---|
Now, we move all the terms to one side of the equation. |
So, we have |
|
We solve to get |
(b)
Step 1: |
---|
First, we find the slope of the tangent line at the point |
We plug into the formula for we found in part (a). |
So, we get |
|
Step 2: |
---|
Now, we have the slope of the tangent line at and a point. |
Thus, we can write the equation of the line. |
So, the equation of the tangent line at is |
|
Final Answer: |
---|
(a) |
(b) |